Dare to jump: The effect of the new high impact activity SuperJump on bone remodeling. A new tool to maintain fitness during COVID-19 home confinement - Vasto, S.; Amato, A.; Proia, P.; Caldarella, R.; Cortis, C.; Baldassano, S. (Biology of Sport, 2022)
SuperJump is a high impact activity performed on an elastic trampoline that mixes aerobic and anaerobic exercises already proposed as home-based activity for preventing a sedentary lifestyle. We determined in a randomized controlled trial whether 20 weeks of SuperJump activity would promote bone formation and reduce resorption in eumenorrheic women. Twenty-four women were randomized to a non-exercise group (control group) or an exercise group that performed SuperJump activity three times a week for 20 weeks. Blood samples were collected in both groups at baseline and at the end of the 20 weeks and compared within and between the groups for C-terminal telopeptide (CTX), a marker of bone resorption, osteocalcin, a marker of bone formation, and the markers of bone metabolism parathyroid hormone (PTH), calcitonin, albumin-adjusted calcium (Aa calcium), vitamin D, phosphate and potassium. After 20 weeks of SuperJump activity, levels of CTX were significantly reduced while levels of osteocalcin were increased. PTH, calcium and potassium were involved in the mechanism of action because PTH was reduced while calcium and potassium were increased. Calcitonin, vitamin D and phosphate levels did not change. These data suggest that SuperJump activity is able to reduce bone resorption and improve bone formation by acting on essential regulators of bone metabolism. They also suggest that SuperJump training may be used as a valuable intervention to prevent the occurrence of osteoporosis in aging because it improves bone homeostasis in favor of bone formation and could counteract a sedentary lifestyle, such as during COVID-19 home confinement, which could itself contribute to the variation of bone metabolism. Trial registration: Clinicaltrials.gov NCT04942691 -retrospectively registered.